Comparative Analysis Of Stock Price Dan Volume Before And During Covid-19 Pandemic At PT. Kalbe Farma Tbk - Rahma Gusmawati Tammu; Elisabet Pali; Resinta (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to analyze the comparison of stock prices and volume at PT. Kalbe Farma Tbk before and during covid-19 pandemic. Type of this research used is descriptive quantitative analysis. Data analysis techniques using Paired Simple T-Test with SPSS 25. Based on the results of the Paired Sample T-Test on the stock price of PT. Kalbe Farma Tbk can be concluded that the significance value is 0.733 (p > 0.05). So Hi is rejected, Ho is accepted, which means there is no significant difference to the stock price of PT. Kalbe Farma Tbk, before and during the covid-19 pandemic. Based on the results of the Paired Sample T-Test on the stock volume of PT. Kalbe Farma Tbk can be concluded that the significance value is 0.043 (p < 0.05). So, Hi is accepted, Ho is rejected, which means that there is a significant difference in share volume.